Histopathological Observation of the Intestine of Capra hircus (L.) Infected with Cotylophoron cotylophorum (Stiles et Goldberger, 1910) - M. N. Kadam2, Nitin Padwal1* (Recent Research in Science and Technology, 2011)
The present investigation deals with the histopathological observation of the intestine of Capra hircus (L.) infected with the trematode parasites Cotylophoron cotylophorum [11] is having muscular sucker which is used for attachment to the intestine of host Capra hircus (L.). In T.S. of intestine of Capra hircus (L.), it has been observed that the Cotylophoron cotylophorum attached to the different layers of intestine and slowly damaged the hosts intestinal tissue and it destroys the intestinal epithelium of villi showing trematodes are highly destructing the intestine of Capra hircus (L.).